Haptic Interaction Perception, Devices and Algorithms - Kajimoto, Hiroyuki; Lee, Dongjun; Kim, Sang-Youn; Konyo, Masashi; Kyung, Ki-Uk (Lecture Notes in Electrical Engineering,, 2019)
This book constitutes the proceedings of the third international conference AsiaHaptics 2018, held in Songdo, Korea. It presents the state-of-the-art of the diverse haptics (touch)-related research, including perception and illusion, development of haptics devices, and applications to a wide variety of fields such as education, medicine, telecommunication, navigation and entertainment. This book is a valuable resource not only for active haptics researchers, but also for general readers wishing to understand the status quo in this interdisciplinary area of science and technology.